TINGKAT PENGETAHUAN TENTANG PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK BERDASARKAN KARAKTERISTIK IBU HAMIL - Rahayu, Tri Budi (Media Ilmu Kesehatan, 2017)
Background : High maternal mortality rate is a problem and a concern for all countries due to the impact effect on the economy, politics and policy development. As one of the efforts to reduce maternal mortality and infant mortality rate in Indonesia, KIA book as means of integration of maternal and child health services. Lack of knowledge of pregnant women about the KIA books utilization can increase the risk of maternal and infant mortality. Objective : This study aimed to determine the level of knowledge about the utilization of KIA book in pregnant women. Methods : This research was descriptive quantitative with cross sectional data collection. Univariat analysis was used for the data analysis. The sampling technique was total sampling with the number of 48 pregnant women. Results : The result of univariate analysis showed that 65% pregnant women had enough knowledge about the utilization of KIA book. Conclusion : The level of knowledge about the utilization of KIA book is categorized into enough category. Keywords : knowledge, KIA book